전이성 전립선암에 의한 이소성 부신피질자극호르몬 증후군 1예 - 김은기; Eun Ky Kim; 곽수헌; Soo Heon Kwak; 안화영; Hwa Young Ahn; 강아름; Ah Reum Khang; 박효진; Hyo Jin Park; 박소연; So Yeon Park; et al. (Endocrinology and metabolism (Seoul), 2012)
이소성 부신피질자극호르몬(adrenocorticotropic hormone, ACTH) 분비는 주로 신경내분비종양, 폐소세포암과 연관되나 드물게 전립선암과 연관되어 불량한 예후를 보인다고 보고된다. 저자들은 전이성 전립선암 환자에서의 이소성 ACTH 분비를 발견하였다. 3년간의 호르몬 치료에도 진행한 전이성 전립선암으로 고식적 전립선 수술을 받은 70세 환자에서 패혈성 쇼크가 발생하였다. 적절한 치료에도 지속되는 발열 및 전신 상태 악화로 측정한 혈중 기저 ACTH 및 코르티솔의 상승으로 이소성 ACTH 분비가 의심되었으나 급격한 다발성장기 부전으로 사망하였다. 환자는 쿠싱증후군의 외형은 뚜렷하지 않았으나 고혈압의 병력과 저칼륨혈증이 있었다. 전립선 수술 조직에서 선암과 소세포암이 혼재되어 있었으며 소세포암은 chromogranin 발현 증가, ACTH의 국소적 양성, 전립선특이항원(prostate specific antigen) 음성을 보였다. 이에 전립선암 환자에서 임상적 특징에 따라 이소성 ACTH 분비를 드문 감별 진단으로 고려하여야 할 증례로 보고하는 바이다. Ectopic adrenocorticotropic hormone (ACTH) syndrome is mostly associated with neuroendocrine tumors and small cell carcinoma of the lung. This syndrome of prostate cancer is rare and has been reported in only a few cases. We report a patient with ectopic ACTH production associated with metastatic prostate cancer. A 70-year-old patient with metastatic prostate cancer was admitted to our hospital with septic shock. He had a history of hormonal therapy and transurethral prostatectomy. Adrenocortical function was checked due to consistent fever and poor general condition, which revealed markedly increased levels of basal plasma ACTH and serum cortisol. The patient did not present typical signs of the Cushing`s syndrome, however, hypokalemia and a history of hypertension were found. He died in days as a result of multi-organ failure. On pathology, the prostatectomy specimen showed a tumor composed of mixed populations of adenocarcinoma and small cell carcinoma. The tumor cells in the small cell component were positive for chromogranin and ACTH. Although neuroendocrine differentiation in prostate cancer is rare, etopic ACTH production should be considered in patients with prostate cancer as well as in clinical features of ACTH hypersecretion.